Relationship between soundscapes and landscape factors in urban commercial spaces - Hong, Joo Young (2017)
This study aims to explore the relationship between soundscape and landscape factors in commercial spaces. Commercial pedestrian streets in Seoul, Korea were selected in order to include various sound and visual elements in urban commercial spaces. In site evaluation of soundscape were performed in the case study areas. Perceptual and physical acoustic environments in the commercial area were assessed using both questionnaire surveys and acoustic measurements. In terms of landscape factors, urban morphological indices and event density of street were calculated to analyze the visual environments and behavioral characteristics of pedestrians in commercial area. Based on the field measurement data, the effects of landscape factors on soundscape perception in urban commercial streets were examined.